Causes of adult mortality in two populations of New Zealand sea lions (Phocarctos hookeri). (June 2019) - Lenting, B.; Gartrell, B.; Kokosinska, A.; Duignan, P.J.; Michael, S.; Hunter, S.; Roe, W.D.
Highlights: Infectious disease, including tuberculosis, was the most common cause of death. Anthropogenic trauma caused 26% of deaths in mainland sea lions. Trauma inflicted by adult male conspecifics caused 24% of deaths. Abstract: The New Zealand sea lion is an endangered species endemic to New Zealand. While causes of death are well described for pups of this species, mortality in adults is poorly characterised. This study investigated causes of death in 136 New Zealand sea lions in two different populations: a major breeding site on remote, uninhabited Enderby Island in the sub-Antarctic, and a slowly increasing recolonising population on the inhabited mainland. For animals with at least a partial diagnostic investigation ( n = 112), the most frequently diagnosed causes of mortality were infectious disease (41/112; 37%), particularly tuberculosis due to M. pinnipedii (20/112; 18%), and conspecific trauma (27/112; 24%). Anthropogenic trauma was an important cause of death in mainland sea lions (9/33; 26%). Deliberate anthropogenic mortality has previously been identified as the greatest potential threat to population recovery for mainland sea lions, and as human and pinniped populations increase, managing interactions between these species will become increasingly important.